Centralized and decentralized utilization of organic residues for lactic acid production. (20th January 2018) - Venus, Joachim; Fiore, Silvia; Demichelis, Francesca; Pleissner, Daniel
Abstract: Depending on the source, the composition of organic waste can be heterogeneous. A mixture of organic waste and food waste appearing in urban areas was estimated to contain in average 550 kg t −1 carbohydrates (including 400 kg t −1 starch), 119.1 kg t −1 lipids and 54 kg t −1 proteins. Contrarily, the organic waste produced by fruits and vegetables processing industry is predictable in quality and quantity. This study considers the production of lactic acid from waste organic material using one-step or two-step approaches. One-step approaches are based on simultaneous hydrolysis and fermentation, while in two-step approaches both are carried out sequentially. It is recommended to implement one-step and two-step processes for an on- and off-site utilization of organic waste, respectively. The scenarios sketched are based on organic waste produced by hotels and in urban areas, and organic waste produced by fruits and vegetables processing industries. It is argued that a decentralized one-step process is appropriate at locations, such as food and vegetables processing industries, where sufficient organic waste is formed and interest in using the bio-based products exists. While two-step processes are to implement at locations where organic and inorganic waste streams are mixed and quality and quantity vary. It is further argued that a decentralized utilization may not end with a final product, but with an easy transportable solution containing either convertible nutrients or the lactic acid containing fermentation broth serving as feedstock to relevant industries. The sketched scenarios are not limited to lactic acid, but can be considered for other biobased products whose production contributes to sustainability and bioeconomy.